2010
DOI: 10.1590/s0004-282x2010000300018
|View full text |Cite
|
Sign up to set email alerts
|

Supra-orbital keyhole removal of anterior fossa and parasellar meningiomas

Abstract: The improvement of surgical techniques as well as the introduction of new surgical instruments promoted the use of keyhole craniotomies in neurosurgery. We evaluated the technical aspects of the supra-orbital keyhole approach considering the indications, limitations, and complications of this approach to treat anterior cranial fossa and parasellar meningiomas. Twenty-four patients (21 females; mean age, 53±8.6 years) operated on between 2002 and 2006 through a supra-orbital eyebrow approach were studied. Maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
0
15
0
2
Order By: Relevance
“…However, only eight patients (2.3%) developed rhinoliquorrhea, and only one patient (0.3%) meningitis, which is a very low percentage and also significantly lower than rates reported by Paiva-Neto and Tella. 1 The reason could be the extended experience with this approach at our institution, reducing the rate of significant complications. Data of the present study also showed that if a rhinoliquorrhea due to a breach of the FS occurs, a surgical revision is always required to close the fistula permanently as none of the patients benefited from a lumbar CSF drain alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only eight patients (2.3%) developed rhinoliquorrhea, and only one patient (0.3%) meningitis, which is a very low percentage and also significantly lower than rates reported by Paiva-Neto and Tella. 1 The reason could be the extended experience with this approach at our institution, reducing the rate of significant complications. Data of the present study also showed that if a rhinoliquorrhea due to a breach of the FS occurs, a surgical revision is always required to close the fistula permanently as none of the patients benefited from a lumbar CSF drain alone.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of CSF rhinorrhea after this type of craniotomy was recently reported to range from 0% to 9.1%. 1,2 Even though a CSF fistula is not considered a major compli-cation, it bears the potential risk for the patient to develop meningitis. This also can negatively influence the patient's recovery and therefore the overall surgical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Our literature search revealed 1,026 TSMs in 32 published series resected using transcranial surgery since 2000 (►Table 2). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][31][32][33][34][35][36][37][38][39][40][41][42] The surgical approach was pterional in 541 (52.7%), unilateral subfrontal in 129 (12.6%), bilateral subfrontal in 81 (7.9%), supraorbital in 123 (12.0%), interhemispheric in 41 (4.0%), and other or not specified in 111 (10.8%). Overall, 85% of surgeries achieved GTR, defined as Simpson Grade I or II, out of the 993 for which this data was reported.…”
Section: Transcranial Surgerymentioning
confidence: 99%
“…33 However, frontal brain retraction may still be required, and the operative corridor can require manipulation of the ipsilateral optic nerve and carotid, which are between the operator and the tumor. 33,35 Recently, there has been interest in the use of the supraorbital approach as a less-invasive alternative to typical transcranial methods, either through a supraorbital keyhole 18,19,31,38 or as modification of the pterional approach. 17 The supraorbital keyhole employs microsurgery and/or endoscopy to reduce the size of the craniotomy and reduce postoperative discomfort.…”
Section: Transcranial Surgerymentioning
confidence: 99%
See 1 more Smart Citation